2007
DOI: 10.1152/ajpendo.00565.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acylation-stimulating protein/C5L2-neutralizing antibodies alter triglyceride metabolism in vitro and in vivo

Abstract: August 21, 2007; doi:10.1152/ajpendo.00565.2006.-Acylation-stimulating protein (ASP), a lipogenic hormone, stimulates triglyceride (TG) synthesis and glucose transport upon activation of C5L2, a G protein-coupled receptor. ASP-deficient mice have reduced adipose tissue mass due to increased energy expenditure despite increased food intake. The objective of this study was to evaluate the blocking of ASP-C5L2 interaction via neutralizing antibodies (anti-ASP and anti-C5L2-L1 against C5L2 extracellular loop 1). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 46 publications
6
35
0
Order By: Relevance
“…Further, additional studies with transfected cells indicated the ability of C5L2 to bind and transduce signals in response to C3a, C4a, and their des-arginine derivatives (9,11,36,37). Some of these discrepancies have subsequently been resolved (6,38).…”
Section: Discussionmentioning
confidence: 99%
“…Further, additional studies with transfected cells indicated the ability of C5L2 to bind and transduce signals in response to C3a, C4a, and their des-arginine derivatives (9,11,36,37). Some of these discrepancies have subsequently been resolved (6,38).…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of ligand binding. While a number of blocking antibodies specific for the mouse, rat, or human C5a 2 receptor have been developed and employed by different investigators in vitro and in vivo (Gao et al, 2005;Cui et al, 2007;Lee et al, 2008;Bamberg et al, 2010), to our knowledge the only antagonists for the human C5a 2 receptor are the C5a mutant jun/fos-A8, and its derivative jun/fos-A8 D71-73 , which inhibit ligand binding to both the C5a 1 receptor and C5a 2 receptor (Heller et al, 1999;Otto et al, 2004).…”
Section: A Introductionmentioning
confidence: 99%
“…Thus, the ASP/C5a 2 receptor neutralizing antibodies that effectively block the ASP-C5a 2 receptor interaction altered lipid distribution and energy utilization. Moreover, continuous administration of anti-ASP antibodies as compared with an IgG negative control had effects on energy expenditure and glucose storage, increasing in vivo whole-body energy utilization (Cui et al, 2007;Paglialunga et al, 2010).…”
mentioning
confidence: 99%
“…Activation and phosphorylation of C5L2 leads to increased fatty acid uptake, increased glucose transport, and stimulation of diacylglycerol acyltransferase activity (9,10,19,20). ASP is produced through cleavage of the precursor protein complement C3 via factor B and adipsin (factor D) interaction generating C3a, which is rapidly desarginated to produce ASP (also known as C3adesArg) (6, 25).…”
mentioning
confidence: 99%